Development of technology for deposition of thick copper layers onto ceramic substrates applied in power electronics - Yuri K. Nepochatov; Pyotr M. Pletnev; Vladimir F. Kosarev; Tatiana S. Gudyma (Chimica Techno Acta)
The basic element of the design of a power module is a metallized ceramic substrate. In this work, the formation of metallization coatings by the method of thermal transfer of metallization pastes (Mo-Mn-Si + binder) for alumina and aluminum nitride ceramics was carried out. The fixing of the metallization coating on the ceramic substrate was performed by firing at a temperature of 1320 °C. The subsequent deposition of the copper layer was carried out by the method of cold gas-dynamic spraying (CGDS) followed by annealing of the deposited coating. For high-quality adhesion, the optimum annealing temperature was 1000 °C.